Awareness About Mathematical Patterns in MI Muhammadiyah 3 Jogoroto Jombang Students - Eny Suryowati; Abd Rozak; Eka Agustina Rizkiyati (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
Awareness of patterns in this study is closely related to generalization. This awareness is the condition of someone who can know there is an order in the pattern, can mention the structure of the given pattern and can determine the next pattern. One of the basic skills in learning mathematics is generalization. This research is a descriptive quantitative research that aims to describe awareness of mathematical patterns in grades 4, 5 and 6 of MI Muhammadiyah 3 Jogoroto Jombang. The sample of this research was 89 students in grades 4, 5 and 6 of MI Muhammadiyah 3 Jogoroto Jombang. All students were given questions about number patterns and figure patterns and then conducted interviews. The results showed that students' awareness of number patterns was 80,65% for 4th grade , 95,83% for 5th grade and 97,06% for 6th grade . Meanwhile, students' awareness of figure patterns was 87,09% for 4th grade, 95,83% for 5th grade and 100% for 6th grade. Based on the results of this study, it can be seen that students in grades 4, 5 and 6 of MI Muhammadiyah 3 Jogoroto Jombang are already able to recognize pattern regularity, can mention the pattern structure and can determine the next pattern, which is limited in number. Students have not been able to determine the number of elements (structures) in the n-th pattern.